Management and Development of Scouting Extracurricular Activities - Elce Purwandari; Rambat Nur Sasongko; Muhammad Kristiawan; Zuhri Zuhri; Agung Subakti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the management and development of scout extracurricular activities at SMAN Surulangun, Musi Rawas Utara District. The research subjects consisted of 3 informants. The main informant consisted of 1 person, namely the scout extracurricular coach, the key informant consisted of 1 person, namely the head of SMA Negeri Surulangun, and additional informants consisted of 1 person, namely a student of SMA Negeri Surulangun. The research method used is a qualitative descriptive method. Data collection techniques in this study use observation, interviews, and documentation. Data collection method using triangulation. The results showed that SMAN Surulangun had carried out the management and development of extracurricular activities well, which consisted of planning, staffing and personnel management, and financial budgeting. The planning begins with the formation of an organizational structure for the scout extracurricular management so that each manager works according to their respective main duties and functions. Furthermore, making short, medium, and long term work programs so that scout extracurricular activities are directed according to the goals to be achieved. In the process of achieving the planned program objectives, cooperation from various parties is needed, for example, cooperation in the form of sponsorship of activities. At the Staff and Personnel Arrangement stage, recruited coaches must have a certificate of at least Basic Advanced Course (KMD) while for activity managers, at least they have been appointed as Bantara enforcers. At the Financial Budgeting stage, the main source of funds obtained by current managers or schools in organizing scout extracurricular activities at SMAN Surulangun is BOS funds. The form of accountability for the manager/trainer is to make and compile an accountability report (LPJ) for the scout extracurricular activity development program at the end of each activity and at the end of each management session during the deliberations of the troop which is intended for the school principal as kamabigus.